Mining for Christ: Eco-Justice in Contexts of Resource Extraction - Pranger, Jan Hendrik (Interreligious Studies and Intercultural Theology, 2019)
This article discusses the social and ecological impacts of fracking for oil on religious communities in Western North Dakota. Attention is furthermore given to racial tensions between the settler and indigenous communities that have become pronounced within churches in relation to the repudiation of the discovery doctrine and the protests at the Standing Rock Reservation against the North Dakota Access Pipeline in the fall of 2016.